Chief Red Cloud, 1822-1909 - Monroe, Judy (Mankato, Minn. : Blue Earth Books, 2004)
A biography of Chief Red Cloud, the Lakota leader who successfully forced the United States Army to close the Bozeman Trail, which crossed ancestral lands and endangered hunting grounds and sacred sites. Includes instructions for making an animal sign and a recipe for Sioux Indian Pudding.
Battle of the Hundred Slain -- Life on the Great Plains -- Growing up Lakota -- Becoming a warrior -- A Lakota leader -- Broken promises.
Includes bibliographical referenes and index.
1060L
Keywords: Red Cloud -- 1822-1909; Oglala Indians -- Kings and rulers; Red Cloud's War -- 1866-1867; Bozeman Trail -- History; Oglala Indians; Indians of North America -- Great Plains; Kings, queens, rulers, etc